The area bounded by the graphs \[y=\sqrt{2-x^2} \qquad \text{and} \qquad x+\left(\sqrt{2}-1\right)y=\sqrt{2}\] equals

\(\dfrac{\sin{\sqrt{2}}}{\sqrt{2}}\);

\(\dfrac{\pi}{4}-\dfrac{1}{\sqrt{2}}\);

\(\dfrac{\pi}{2\sqrt{2}}\);

\(\dfrac{\pi^2}{6}\).

The area bounded by the graphs \[y=\sqrt{2-x^2} \qquad \text{and} \qquad x+\left(\sqrt{2}-1\right)y=\sqrt{2}\] equals

\(\dfrac{\sin{\sqrt{2}}}{\sqrt{2}}\);

\(\dfrac{\pi}{4}-\dfrac{1}{\sqrt{2}}\);

\(\dfrac{\pi}{2\sqrt{2}}\);

\(\dfrac{\pi^2}{6}\).